Acessibilidade em websites de comércio eletrônico: avaliação através da interação com usuários cegos. - Guimarães, Ítalo José Bastos (2016)
This study presents an approach about the accessibility in e-commerce, whose research objective is to outline its structure through interaction with blind users in most accessed websites in Brazil, like Americanas.com, Neshoes.com.br and Walmart.com.br. Among the methodological aspects, was adopted the review literature with the realization of an exploratory and descriptive research through one qualitative and quantitative approach. The deployment of this research was divided into two stages: (1) automatic accessibility evaluation on websites that are part of the search and (2) accessibility test with five blind users divided into three tasks, namely: recognition navigation, search a product on the website and realize the purchasing procedures. For aspects related to the understanding of visual impairment, the concept of blindness was defined and explained specific aspects related to its classification and causes, as well as presenting the main legislation in force in the country and the use of technologies such as social inclusion. The accessibility as support for blind users on the web is approached with the purpose of deepening the theme, as well as major initiatives undertaken by international and national institutions. It also presents aspects related to e-commerce in Brazil, in which it discusses its concepts and characterization, describes the overview of the electronic market in Brazil and lists the main websites, considering the number of access. The automatic accessibility test reports showed that the websites analyzed did not pass by the test battery with a minimum level recommended by WCAG 2.0. In addition, the results with the user test showed that the websites have accessibility barriers that hindered navigation blind users in the analyzed pages, making it impossible, at least one user, to complete the purchase procedures. Therefore, are needed changes in the structure of pages tested with the objective of correcting the barriers reported in this study. Thus, companies involved in the study should understand the differences between the navigation of the blind users and sighted users, in order to provide inclusive and accessible digital information environments.